Case studies in physiotherapy - Justine, Maria (UiTM, 2013)
Case studies in Physioterapy consist of common conditions in musculosketel, neurology, cardiorespiratory as well as geriatric cases that may be encountered by students during their clinical placement in various hospitals. it was written as such to help students to develop skills in patients assessment, and to deliver safe and effective treatment as a preparation prior to clinical placement. The review questions provided will also guide students to develop skills in problem solving approaches based on clinical reasoning and research evidence. This book can be used by students undergoing diploma and bachelor level as well as qualified physiotherapist as a refresher course.